Transient Destabilization of Declarative Memory—Opposing Impact of Physical Exercise or Rest after Encoding in Typically Developing Children and Children with Attention Deficit Hyperactivity Disorder but No Difference after Subsequent Sleep - Manuel Munz; Lioba Baving; Alexander Prehn-Kristensen (Brain Sciences, 2022)
Background: Children are especially sensitive to a broad range of influences and show a remarkable capacity for learning. One prominent example is declarative memory, which may be influenced by a variety of factors and is impaired in attention deficit hyperactivity disorder (ADHD). Exercise and sleep, or both combined, might foster declarative memory. Methods: Here, 12 typically developing children (TDC) and 12 age-matched children with ADHD participated in an exercise and rest condition before a night in the sleep laboratory. Declarative memory was encoded before exercise or rest and retrieved before and after a night of sleep. Results: Exercise in TDC but rest in ADHD lead to a transient destabilization of declarative memory, while there were no more differences after a night of sleep. Rapid eye movement (REM) sleep latency was prolonged after exercise in both groups. Conclusions: Exercise leads to opposing effects on immediate declarative memory formation. The factors or contexts that promote or hinder declarative memory formation in children ADHD and TDC differ, and further work is needed to determine the recommendations for declarative learning in children with ADHD.